Nivel de información y actitudes sobre la infección y prevención del virus del papiloma humano en grupos de diferentes niveles de instrucción - Revier Palacios, Karla Emily (2014)
The human papillomavirus is a necessary but not sufficient for cervical cancer, but yet is very attached to him, reason needed to be well informed on the subject and guide against certain attitudes in the population to counter: infection prevention, and health maintenance. The objective of this research was "Determine the level of information and attitudes about the infection and prevention of human papilloma virus in groups of different levels of instruction"; for which students took as reference mde tenth race of Medicine, Law and residents of Tierras Coloradas randomly chosen neighborhood. The results obtained are: a knowledge " under" 51.11 % and an " unfavorable attitude " 57.78 % against infection and prevention of human papilloma virus in the respondents, with the exception of students in human medicine was found. Regarding risk factors, it appears that most recognize the factors proposed; 48.89 %, very important point for prevention. Preventive attitudes to infection were: vaccine acceptance 86.67 %, not performing Pap 51.22 % and the rejection of condom use 53.33 %. It was also observed that do not recognize infection Human Pap Virus and Cervical Cancer generating 51.11 %. Keywords: human papillomavirus, knowledge, attitudes, vaccine, cancer prevention.